CdTe quantum dots film by electrospinning as bearing temperature sensor. Issue 1 (March 2021) - Pan, Zhang; Ke, Yan; Jun, Hong; Zhu, Yongsheng
Abstract: Temperature monitoring of bearing rotating elements is crucial for bearing condition assessment and early warning. Using CdTe quantum dots (QDs) to prepare sensors requires other membrane material as the substrate, which affects the accuracy of the test. Meanwhile, CdTe QDs exposed to air for long time will lead to oxidation, which affects the storage life of the sensors. Hence, based on excellent film forming properties of polyvinyl alcohol (PVA), the CdTe/PVA polymeric nanofiber was fabricated by electrospinning method. For comparison, the CdTe/PVA composite film by drop-casting method was also prepared. Thermal properties show that there are excellent linear relationships between peak wavelength and temperature of the CdTe/PVA composite film and the CdTe/PVA polymeric nanofiber respectively. However, the uniformity of the CdTe/PVA polymeric nanofiber obviously better than the CdTe/PVA composite film. Outstanding temperature dependence of photoluminescence spectra and uniform film formation demonstrating the potential value of the obtained CdTe/PVA polymeric nanofiber as temperature sensor for bearing rotating elements.